The Effect of Production Input on Corn Farmers’ Income Growth in Karo Land. - Yescenia Sigiro; Eki Monalisa Br Surbakti; Siska Lumban Batu; Yohanna Sitanggang; Cristina Martalia Sitepu; Evi Syuriani Harahap (Edumaspul: Jurnal Pendidikan, 2025)
This study aims to determine the effect of production inputs on the income growth of corn farmers in Tanah Karo Regency. The research method used a quantitative approach, with 50 corn farmers as respondents. Data were collected through questionnaires and analyzed using simple linear regression. The results showed that production inputs (capital, seeds, fertilizer, and labor) had a positive and significant effect on increasing corn farmers' income. The coefficient of determination of 0.682 indicates that 68.2% of income variation is influenced by production inputs.